Pengembangan Perangkat Pembelajaran Model Cooperative Tipe Two Stay Two Stray Berbasis Tradisi Upacara Benyaru untuk Meningkatkan Kompetensi Peserta - Yuni Nur Hidayati; Warsono Warsono; Ismet Basuki (LP. Ma'arif Janggan Magetan, 2023)
This research aims to develop learning tools using the Two Stay Two Stray Cooperative Model Based on the Benyaru Ceremony Tradition to Improve Participants' Competence. This study uses a development design adopted from 4D design, namely Define, Design, Develop and Disseminate. The results of the development show that the progress achieved on the LKS instrument has produced teaching materials and lesson plans that meet the criteria. valid and can be used as a learning tool. The results of the research attitude competency test show an increase in learning outcomes at SMPN 1 Long Ikis (which is used as an exam school) as well as at SMPN 2 Long Ikis and SMPN 5 Long Ikis. The knowledge competency research shows better learning outcomes both at SMPN 1 Long Ikis, as well as at SMPN 2 Long Ikis and SMPN 5 Long Ikis, this supports this. This is clear because the attitude scores and learning outcomes have exceeded the KKM. Based on the attitude competency test, learning outcomes have increased at SMPN 1 Long Ikis (which was used as a trial school) as well as at SMPN 2 Long Ikis and SMPN 5 Long Ikis.